Ecological Tax Reform and Unemployment - Oliver Budzinski (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2002)
The question of a double dividend from revenue-neutral ecological tax reforms (an ecological advantage plus an economic advantage) has recently become a widely discussed topic both in real-world economic policy and in economic theory. The subject has produced many advocates and opponents in the scientific community. This paper examines potential economic dividends from revenue-neutral ecological tax reforms by systematically distinguishing between an efficiency dividend and an employment dividend. Their occurrence is discussed from the viewpoint of two different theoretical approaches: namely, the optimal taxation view and the market process view. According to the optimal taxation view, which dominates recent economic analysis on this subject, an efficiency dividend seems doubtful whereas an employment dividend is likely to occur under specific circumstances (e.g. involuntary unemployment and sub-optimal initial tax system). However, there is a considerable number of unsuitable assumptions which create doubt when questioning how appropriate the use of optimal taxation theory is when discussing real-world ecological tax reforms. The market process view enlarges the analysis by integrating effects on and from competition and innovation. This strengthens the occurrence of an employment dividend in an imperfect world with involuntary unemployment. In this framework the reduction of involuntary unemployment results from declining wage costs which boost labour demand, a shift in the bias of the innovation process, and an evolution of the consumption basket because of changing relative prices.
Keywords: Q48; H21; 330; environmental taxation; double dividend; market process theory; involuntary unemployment